(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study investigates the job performance of employees in public and private sector hospitalsin India. It aims to compare the factors influencing job performance and assess the differences betweenthe two sectors. The study utilizes a mixed-method approach, including surveys and interviews, tocollect data from employees across multiple hospitals. The findings reveal that while both public andprivate sector hospitals prioritize job performance, there are notable variations in the factors thatcontribute to it. Public sector hospitals emphasize job security, seniority-based promotions, andadherence to regulations as crucial drivers of job performance. In contrast, private sector hospitalsfocus on performance-based incentives, career growth opportunities, and a competitive workenvironment. The study highlights the significance of aligning organizational practices with employeeexpectations to enhance job performance and suggests recommendations for improving performancemanagement systems in both sectors